2015
DOI: 10.1038/cddis.2015.105
|View full text |Cite
|
Sign up to set email alerts
|

Bid chimeras indicate that most BH3-only proteins can directly activate Bak and Bax, and show no preference for Bak versus Bax

Abstract: The mitochondrial pathway of apoptosis is initiated by Bcl-2 homology region 3 (BH3)-only members of the Bcl-2 protein family. On upregulation or activation, certain BH3-only proteins can directly bind and activate Bak and Bax to induce conformation change, oligomerization and pore formation in mitochondria. BH3-only proteins, with the exception of Bid, are intrinsically disordered and therefore, functional studies often utilize peptides based on just their BH3 domains. However, these reagents do not possess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
114
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(124 citation statements)
references
References 57 publications
(118 reference statements)
8
114
1
1
Order By: Relevance
“…In Jurkat and SKW6.4 cells, the tolerance for BIK, BMF or NOXA is similar to that of BIM EL or PUMA (Figures 3k and l), consistent with claims that BIK, BMF and NOXA might also be direct activators in at least some contexts. 2,20,23,52 In contrast, the tolerance for BAD is much higher than the tolerance for BIM and PUMA in all cell lines examined (Figures 3k, 3l, 5b and c). This difference between BAD and the other BH3-only proteins was particularly evident in cells with relatively low expression of BCL2 and BCLX L (Figures 3k and l).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In Jurkat and SKW6.4 cells, the tolerance for BIK, BMF or NOXA is similar to that of BIM EL or PUMA (Figures 3k and l), consistent with claims that BIK, BMF and NOXA might also be direct activators in at least some contexts. 2,20,23,52 In contrast, the tolerance for BAD is much higher than the tolerance for BIM and PUMA in all cell lines examined (Figures 3k, 3l, 5b and c). This difference between BAD and the other BH3-only proteins was particularly evident in cells with relatively low expression of BCL2 and BCLX L (Figures 3k and l).…”
Section: Discussionmentioning
confidence: 83%
“…15,16 Upon activation, the proapoptotic family members BAK and BAX can breach the mitochondrial outer membrane (MOM), leading to cytochrome c release, caspase 9 activation and subsequent apoptotic events. Genetic 2,17 as well as biochemical experiments [18][19][20][21][22][23] have indicated that the BH3-only proteins BIM, PUMA, a protease generated BID fragment (tBID), and, in some studies, NOXA can directly bind and activate BAK and/or BAX. To counteract these effects, antiapoptotic BCL2 family members such as BCL2, BCLX L and MCL1 bind and neutralize activated BAX and/or BAK 2,6,16,24 as well as activated or overexpressed BH3-only family members, [25][26][27][28][29][30] thereby preserving MOM integrity.…”
mentioning
confidence: 99%
“…WT cBID (which lacks cysteine in the activating p15 fragment) and cBID I83C and R84C variants were incubated with cytosolic extracts from cells stably expressing BAK/BAXCS with cysteines engineered in either the groove (H99C or K113C) or α6 (R156C, D160C, or H164C). Disulphide linkage was induced with oxidant [copper (II) (1,10-phenanthroline) 3 , CuPhe] and assessed on nonreducing SDS/PAGE following coimmunoprecipitation. Disulphide-linked cBID:BAK heterodimers were evident between the cBID R84C variant with cysteine at H99 in the BAK groove ( Fig.…”
Section: Bak Conformation Change Destabilizes the Cbid:bak Interactiomentioning
confidence: 99%
“…They are activated by interaction with BCL-2 homology 3 (BH3)-only proteins including BID and BIM (3). Structures show that peptides based on the BH3 domains of activator BH3-only proteins can bind directly to BAK and BAX via a hydrophobic groove (comprising α-helices 2-5) that is also shared with their prosurvival homologs (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Addition of substoichiometric amounts of a "direct activator" BH3-only protein or BH3 peptide induces potent BAX activation, including membrane insertion, oligomerization, and membrane permeabilization, blocked effectively by BCL-X and the like (Kuwana et al 2005;Lovell et al 2008). However, over the years, the list of BH3-only proteins with "direct activator" potential became increasingly long (adding PUMA, BMF, and NOXA, leaving only BAD, BIK, and HRK as "sensitizers" behind), suggesting that experimental design can strongly impact BH3 peptide or BH3-only protein-mediated BAX/ BAK activation or MOMP in in vitro assays (Hockings et al 2015).…”
mentioning
confidence: 99%